Smart cities, regulatory framework in Colombia - Ortega Sanchez , Paola Astrid; Salazar, Hugo Felipe; Fernández González, Herman Antonio (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2020)
This paper presents a literature review of the regulatory and normative aspects that have been developed under the concept of smart cities in Colombia. Through the Ministry of Information and Communication Technologies (MinTIC, Ministerio de Tecnologías de la Información y las Comunicaciones) has been proposed to develop a public policy in order to standardize the implementation of technology in several sectors of Colombian society over the next five years. In this sense, it has been synthesized the aspects to regulate in accordance with the seven components proposed by MinTIC: competitiveness, coexistence, culture, habitat, Infrastructure, resources and services, making a brief description of the regulatory framework that could apply to each of these components.